The end-state L2 acquisition of binding properties of English reflexives by adult Turkish learners of English - Tanış, Fatma. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2007., 2007)
This thesis investigates the end-state second language acquisition (L2) of binding properties of English reflexives by adult Turkish learners to address the issue of UG availability in the end-state L2 grammar. According to the Full Access Model, L2 learners have direct access to innate principles and parameters of Universal Grammar (UG) from the initial state to the end-state in the process of L2 acquisition. Following this model, in this thesis, I predict that L2 learners, having direct access, to UG will acquire binding properties of L2 English reflexives. That is, the end-state L2 grammar of adult Turkish learners of English will converge on native English norms with respect to reflexive binding. 35 adult Turkish speakers of L2 English participated in this study. They were all English language teachers who are considered to be end-state L2 speakers. In addition, in the control group, there were 20 native speakers of English. A grammaticality judgment task and a story-based truth-value judgment task were used to examine whether the end-state L2 grammars of the adult Turkish learners of L2 English are governed by the principles and parameters of UG in the context of reflexive binding. The results of the two tests suggest that the L2 learner’s grammar is UG-constrained and that despite some differences between the L1 and L2, L2 learners can accomplish the acquisition of L2 features in the end-state L2 grammar.
Keywords: Second language acquisition.; English language -- Study and teaching -- Foreign speakers.; Language and languages -- Study and teaching.; Grammar, Comparative and general -- Reflexives.